2013
DOI: 10.4103/0975-7406.113304
|View full text |Cite
|
Sign up to set email alerts
|

Application of ozone in the treatment of periodontal disease

Abstract: Gingivitis and periodontitis are most common inflammatory diseases of supporting tissues of teeth. Role of microbial etiology and host response in progression of gingival and periodontal diseases has been well established. Because of the beneficial biological effects of ozone, due to its antimicrobial and immunostimulating effect, it is well indicated in the treatment of gingival and periodontal diseases. The objective of this article is to provide a general review about clinical applications of ozone in treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1
20

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 11 publications
1
57
1
20
Order By: Relevance
“…Our previous reports have elucidated that the same concentration of ozone gel promotes secretion of collagen matrix and suppresses LPS-induced IL-6 and IL-8 expression without exhibiting cytotoxicity to human gingival fi broblasts 20) . Although it is diffi cult to directly link the results of in vitro and in vivo experiments, our results suggest that ozone gas, ozone water, ozone-olive oil 30) , and ozone gel may be used as therapeutic agents for periodontal disease. However, such applications will require detailed evaluation, such as assessment of biological safety using animal models and functional studies on its long-term eff ects in terms of cellular damage.…”
Section: Pao-li Wang Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous reports have elucidated that the same concentration of ozone gel promotes secretion of collagen matrix and suppresses LPS-induced IL-6 and IL-8 expression without exhibiting cytotoxicity to human gingival fi broblasts 20) . Although it is diffi cult to directly link the results of in vitro and in vivo experiments, our results suggest that ozone gas, ozone water, ozone-olive oil 30) , and ozone gel may be used as therapeutic agents for periodontal disease. However, such applications will require detailed evaluation, such as assessment of biological safety using animal models and functional studies on its long-term eff ects in terms of cellular damage.…”
Section: Pao-li Wang Et Almentioning
confidence: 99%
“…Previously, we reported the safety evaluation of ozone for the skin and eye, as well as its antimicrobial eff ects and role in hemostasis using ozone gel [10][11][12] . In addition, a number of reports have shown that ozone can ameliorate periodontal diseases [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Kanın dokulara oksijen bırakma yeteneğini sağlayan 2,3 DPG (difosfogliserat) miktarında artış meydana gelir. Bu da oksijenin iltihaplı dokuya geri dönmesine imkân tanır 10,13 . Ozon, nitrözoksit gibi damar genişleticilerin salgılanmasına neden olur.…”
Section: Biyolojik Etkileriunclassified
“…16 Ozon yüksek konsantrasyonda immün-depresif, düĢük konsantrasyonda ise immünstimülatif etkiye sahiptir. 17 Ozon dolaĢımdaki oksijenin taĢınmasına yardımcı olmaktadır. Süperoksit dismutaz, katalaz, dehidrogenaz, glutatyon peroksidaz enzimleri düĢük dozdaki ozonla aktive olmaktadır.…”
Section: Introductionunclassified